A new possible way of anthracycline cytostatics decontamination. (26th April 2017) - Štenglová Netíková, Irena R.; Slušná, Michaela; Tolasz, Jakub; Št'astný, Martin; Popelka, Štěpán; Štengl, Václav
Abstract : Cytostatics decontamination based on using an active sorbent of titania, which can adsorb and completely degrade anthracycline anticancer drugs. Abstract : The widespread use of cytotoxic drugs in the treatment of cancer has led to the production of large amounts of contaminated wastes with high exposure risk of medical staff handling cytostatics. For this reason it is essential to use a highly effective and fast decontaminating agent for the decontamination process. Currently used decontamination agents based on NaOCl and NaOH are not sufficient according to our results and also according to literature data. Therefore we have developed a new decontamination agent based on titania nanoparticles, which appears to be a very efficient and fast decontamination agent according to our research data. Anthracycline antibiotics are valuable and frequently used drugs in various chemotherapeutic schemes. They have high efficacy, but also high toxicity, e.g. myelosuppression and cardiotoxicity. They can also act as vesicants in the case of extravasation. Due to their mechanism of action, anthracycline antibiotics have mutagenic and carcinogenic effects. Long term contact, even with a trace amount, can cause changes in human health. Safe decontamination of cytotoxic drug contaminated areas with an agent, which can cause degradation to non-toxic products, is essential. High sorption ability of doxorubicin and epirubicin to titania predisposes TiO2 to become a new, effective and inexpensive agent for area decontamination and degradation of anthracycline antibiotics.